TEACHING ENGLISH AS A FOREIGN LANGUAGE TO DEAF AND HARD-OF-HEARING STUDENTS IN INDONESIAN CONTEXTS - Adnyani, Ni Luh Putu Sri; Wisudariani, Ni Made Rai; Menggo, Sebastianus; Dewi, Kadek Sintya; Wiraningsih, Putu; Xuan, Zhao (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
Due to linguistic difficulties, students with hearing impairments face unique challenges when studying English as a foreign language (EFL). This study examined how hearing-impaired junior high school students in Indonesia were taught and the barriers faced by teachers when teaching students in English. The study employed a descriptive qualitative methodology involving nine teachers from schools for special needs education in Bali. This study applies multiple techniques, including questionnaire distribution, interviews, observations, and document analysis. The study shows the absence of teachers’ prior experience in developing curriculum and syllabus. Other main issues were related to teachers’ and students’ lack of sign language understanding, lack of learning materials, and students’ learning characteristics. The teachers primarily used grammar-translation methods and applied ineffective classroom management. By these findings, policymakers need to review the English curriculum, provide special training for teachers, and design the classroom to satisfy the unique learning needs of the students. Abstrak: Keterbatasan linguistik menyebabkan siswa dengan gangguan pendengaran menghadapi tantangan ketika belajar bahasa Inggris sebagai bahasa asing (EFL). Penelitian ini menganalisis pembelajaran bahasa Inggris untuk siswa tuna rungu pada tingkat SMP serta hambatan yang dihadapi guru ketika mengajar siswa. Penelitian ini menggunakan metode kualitatif deskriptif yang melibatkan sembilan guru dari sekolah luar biasa di Bali. Adapun teknik pengumpulan data yang digunakan adalah penyebaran kuesioner, wawancara, observasi, dan analisis dokumen. Hasil penelitian menunjukkan kurangnya pengalaman guru dalam mengembangkan kurikulum dan silabus untuk pengajaran bahasa Inggris bagi siswa tuna rungu. Masalah lainnya terkait dengan terbatasnya pengetahuan bahasa isyarat oleh guru maupun siswa, ketersediaan materi pembelajaran yang kurang, dan karakteristik belajar siswa yang unik. Guru umumnya menggunakan metode penerjemahan dan penerapan manajemen kelas yang kurang efektif. Sejalan dengan temuan tersebut, pembuat kebijakan perlu meninjau kembali kurikulum bahasa Inggris, memberikan pelatihan untuk guru, serta merancang ruang kelas untuk memenuhi kebutuhan khusus bagi siswa tuna rungu.